Antena Multiple-Input Multiple-Output (MIMO) Array 1×4 Axe Patch Microstip pada Frekuensi 2,4 GHz - Sabtiawan, Thaufiq; Hidayat, M. Reza; Saputera, Yussi Perdana; Somantri, Nivika Tiffany (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2024)
MIMO (Multiple-Input Multiple-Output) Antenna Technology improves wireless network performance by allowing the use of multiple transmit and receive antennas simultaneously. MIMO antennas use antenna elements in an array, such as circular microstrip antennas, to increase signal throughput and reliability. This research simulates and develops a circular microstrip antenna into a 1×4 axe MIMO with array, operating at 2.4 GHz. The simulation shows return loss (S11) -60.913 dB, insertion loss -50.439 dB, VSWR 1.001, bandwidth 116.3 MHz, and gain 5.709 dBi. The results of fabrication and measurement achieve return loss (S11) -61.69 dB, insertion loss -43.16 dB, VSWR 1.00, bandwidth 137.2 MHz at a frequency of 2.4260 GHz. Even though there is a frequency shift of 260 MHz between the simulation and measurement results, the design of this antenna is successful according to the desired specifications.